2002
DOI: 10.1136/fn.86.3.f178
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of a bovine milk formula with an oligosaccharide mixture increases counts of faecal bifidobacteria in preterm infants

Abstract: Background: The establishment of a balanced intestinal microflora which may protect against infection is desirable for the preterm infant. Objective: To investigate the effect of a preterm formula milk supplement consisting of oligosaccharides in similar proportions to human milk on the faecal flora and stool characteristics of preterm infants. Study design: To resemble the effect of human milk, an oligosaccharide mixture consisting of 90% galacto-oligosaccharides and 10% fructo-oligosaccharides was used to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
269
3
17

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(304 citation statements)
references
References 19 publications
15
269
3
17
Order By: Relevance
“…The importance of fibre in alleviating constipation is well known (Taylor, 1990). In addition, GOS are reported to have a bifidogenic effect (Ito et al, 1990;Bouhnik et al, 1997;Boehm et al, 2002;Moro et al, 2002;Knol et al, 2005;Rinne et al, 2005), and here they may have altered bowel function through an increase in bifidobacteria and a change in the colonic environment. However, there were some subjects on whom the GOS had no effect; in fact, their constipation even became more severe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of fibre in alleviating constipation is well known (Taylor, 1990). In addition, GOS are reported to have a bifidogenic effect (Ito et al, 1990;Bouhnik et al, 1997;Boehm et al, 2002;Moro et al, 2002;Knol et al, 2005;Rinne et al, 2005), and here they may have altered bowel function through an increase in bifidobacteria and a change in the colonic environment. However, there were some subjects on whom the GOS had no effect; in fact, their constipation even became more severe.…”
Section: Discussionmentioning
confidence: 99%
“…GOS have been found to relieve constipation in Japanese studies, too (Deguchi et al, 1997;Shitara, 1988). GOS are in general well-tolerated (van Dokkum et al, 1999;Boehm et al, 2002;Moro et al, 2002). However, because of fermentation, symptoms such as abdominal bloating and flatulence may occur in sensitive subjects when large quantities of GOS are ingested (Ito et al, 1990;.…”
Section: Introductionmentioning
confidence: 99%
“…These values have been adopted by the Scientific Committee on Food (SCF: April, 2003) of the European Commission and probably will be implemented in European regulations. In preterm infants, the same mixture of oligosaccharide (1.0 g/100 mL) could stimulate growth of Bifidobacteria and result in stool characteristics as seen in human milk-fed infants [12] . Recently, however, a rat study [14] showed that the intestinal cell wall is irritated and the risk of bacterial translocation increases (following orally Salmonella enteritidis infection) when fructooligosaccharides are provided at a high (3% and 6% of dry matter), but not an unrealistic amount (maximum level adopted by the SCF is about 6% of dry matter).…”
Section: Introductionmentioning
confidence: 99%
“…GOS stimulates intestinal probiotics growth 6565 formula [12,13] , and there is no study using only GOS in infant formula.…”
Section: Introductionmentioning
confidence: 99%
“…Infants ingesting a standard formulae containing FOS+ GOS (0.8g / 100g) induced an increase in faecal bifidobacteria population from 54.8 ± 9.8 to 73.4 ± 4.0 % [68] with a diversity of bifidobacteria species similar to breast-fed infants [127] and stool characteristics identical to those recorded for pre-term infants with human milk [128]. Other infant feeding trials reported an increase in bifidobacteria population by 43-57 % [129] or 59.6 % [130] and the population reached to a level of 10.0 ± 2.05 log cfu/g [131] or 9 x 10 12 cfu/g faeces [115].…”
Section: • Lipid Lowering Actionmentioning
confidence: 94%